ҚАРАҚАЛПАҚ САЗ ӘСБАПЛАРЫ ҲӘМ САЗЛАРЫ - Абдисултанов, Ж. (FAN va JAMIYAT, 2023)
The fact that Karakalpak folk instruments have been preserved for many centuries has facilitated the modification and composition of musical instruments and folk songs.